A Legal Review of Standardized Loan Contracts in Cooperatives: Case Study from the District Court of Kediri - Rokhmatun Hanifah; Adi Sulistiyono; Pranoto Pranoto (Rule of Law Studies Journal, 2025)
Background: Standardized loan agreements are commonly used in cooperatives, but often raise concerns about fairness due to the unequal bargaining position of borrowers. When such contracts are imposed unilaterally, they may contradict principles of consumer protection and contract justice. Aims: This study examines the legal validity of standardized clauses in cooperative loan agreements and evaluates whether such contracts comply with the principle of balance. It also reviews a relevant court decision from the District Court of Kediri. Methods: The research adopts a normative juridical method using statutory, conceptual, and case-based approaches. Legal data were analyzed through deductive reasoning supported by Indonesian civil law, consumer protection law, and cooperative regulations. Result: Findings show that the clauses in question did not qualify as prohibited exoneration clauses under the Consumer Protection Law. The cooperative’s contract fulfilled the formal legal requirements under the Civil Code, and the court upheld its validity, despite the standard nature of the terms. Conclusion: Standard loan agreements in cooperatives are generally considered valid by Indonesian courts, provided they meet formal legal standards. However, to ensure fairness, legal safeguards and better regulatory oversight are needed to protect weaker parties in such contractual relationships.